Loss of RAB39B does not alter MPTP-induced Parkinson’s disease-like phenotypes in mice - Zijie Wang; Zijie Wang; Dingting Yang; Dingting Yang; Yiru Jiang; Yong Wang; Mengxi Niu; Chong Wang; Hong Luo; Huaxi Xu; Jingwen Li; Yun-wu Zhang; et al. (Frontiers in Aging Neuroscience, 2023)
Parkinson’s disease (PD) is a common neurodegenerative movement disorder with undetermined etiology. A major pathological hallmark of PD is the progressive degeneration of dopaminergic neurons in the substantia nigra. Loss-of-function mutations in the RAB39B gene, which encodes a neuronal-specific small GTPase RAB39B, have been associated with X-linked intellectual disability and pathologically confirmed early-onset PD in multiple families. However, the role of RAB39B in PD pathogenesis remains elusive. In this study, we treated Rab39b knock-out (KO) mice with MPTP to explore whether RAB39B deficiency could alter MPTP-induced behavioral impairments and dopaminergic neuron degeneration. Surprisingly, we found that MPTP treatment impaired motor activity and led to loss of tyrosine hydroxylase-positive dopaminergic neurons and gliosis in both WT and Rab39b KO mice. However, RAB39B deficiency did not alter MPTP-induced impairments. These results suggest that RAB39B deficiency does not contribute to PD-like phenotypes through compromising dopaminergic neurons in mice; and its role in PD requires further scrutiny.